Membangun Kepemimpinan Publik Yang Berdampak: Integrasi Nilai Tri Hita Karana Dalam Menjawab Tantangan Kepemimpinan Kontemporer Di Tabanan - I Nyoman Gede Widiana (Universitas Panji Sakti, 2026)
This study aims to analyze the essential qualities and contemporary challenges in building impactful public leadership in Tabanan Regency. Using a qualitative approach through a literature review, five core qualities were identified: (1) transformational vision, (2) effective communication, (3) social concern, (4) ethical courage, and (5) integrity. The main challenges include systemic corruption, socio-economic crises, and digital disruption. Academically, this research proposes a public leadership model that integrates these qualities with the local philosophy of Tri Hita Karana as an operational ethical framework. The findings indicate that integrating the values of Parahyangan, Pawongan, and Palemahan not only strengthens leadership legitimacy but also serves as a contextual foundation for sustainable development. The strategic implications emphasize the need for developing value-based and adaptive leadership capacities to create transformative and responsive leaders at the local level.